The Effect of Financial Depth on Fragile Five Economies - Sökmen, Ferhat Şirin (İdeal Kent Yayınları, 2021)
Improvement in the financial system is important to increase economic growth performance. Because the positive change in the financial system positively affects the investment and consumption decisions ensuring growth. In the meantime, the financial depth that is one of the indicators of financial development measurement is a remarkable index revealing the degree of benefiting from the financial system in terms of developing countries. The entry of both domestic savings and global capital flows into the financial system is crucial to pro-vide the financial depth. This study utilized panel data analysis methods to test the effect of financial depth on economic growth in the light of data of Turkish, South African, Brazilian, Indian, and Indonesian economies that are called fragile five and also well-known with their financial systems’ dependency to external financing for the period between 1980 and 2018. Test results show that it is possible to talk about two-way causality for the country group in the short and long term while there is only a one-way causality from financial depth to Brazilian, Indian, and South African economies.

Finansal sistemdeki gelişme ekonomik büyüme performansının artırılması için önemlidir. Zira finansal sistemdeki pozitif değişim büyümeyi sağlayan yatırım ve tüketim kararlarının verilmesini de olumlu bir şekilde etkileyecektir. Bununla birlikte finansal gelişmişliğin ölçümünde kullanılan göstergelerden bir tanesi olan finansal derinlik, gelişmekte olan ülkelerin finansal sistemden ne derece yararlanabildiğini gösteren önemli bir endekstir. Finansal derinliği sağlamak amacı ile gerek yurtiçi tasarrufların gerekse küresel sermaye akımlarının finansal sisteme girişi önem arz etmektedir.Bu çalışmada finansal derinliğin ekonomik büyüme üzerindeki etkisi “kırılgan beşli” olarak tabir edilen ve finansal sistemlerinin dış finansmana bağımlılıkları ile bilinen Türkiye, Güney Afrika, Brezilya, Hindistan ve Endonezya ekonomilerinde 1980 ve 2018 yılları arasında kalan dönemlere ait veriler ışığında panel veri analiz yöntemleri ile test edilmektedir. Test sonuçları göstermektedir ki, ülke grubunda kısa ve uzun dönemde çift yönlü nedenselliğin varlığından bahsetmek mümkün iken, ülke bazlı analizler sonucunda finansal derinlikten ekonomik büyümeye doğru Brezilya, Hindistan ve Güney Afrika ekonomilerinde tek yönlü bir nedenselliğin bulunduğu söylenebilir.
Finansal Derinliğin Kırılgan Beşli Ekonomileri Üzerindeki Etkisi
Keywords: Sociology (Other); Sosyoloji (Diğer)